Redes de alimentos y producción artesanal en la parroquia Gonzáles Suárez - cantón Otavalo :Un aporte al análisis de la soberanía alimentaria - Lechón Quilumbaquín, Luis Alonso (2015)
This thesis is about a research topic relevant to current events: food networks and their contribution to food sovereignty. The first chapter discusses important definitions by different authors related to food sovereignty, food networks and handicraft production. It also analyzes laws, policies, rights, duties and regulations of food sovereignty that are found in the Constitution, the Organic Law on food sovereignty, in the Organic Code of Territorial Organization, Autonomy and Decentralization, in the National Plan of Good Living 2013-2017, and in the Development Plan of Territorial Order of the González Suárez parish. Chapter II is an analysis of the context of the research. It deals with the geographic location of the González Suárez parish; the population of the communities; the environmental characteristics of the area; the natural resources and territory; the basic services, infrastructure and equipment of the territory the structure of the Provincial, cantonal and parish GAD; the demographic structure: age, sex, education; the ethnic and cultural characteristics; the local economy: agriculture and commerce; the structure of employment, income and poverty; the base, second and third grade organizations. Chapter III presents the findings of the research on food sovereignty in the González Suárez parish, achieved through a qualitative research methodology: interviews, focus groups, observations made among the main community leaders, producing players, collecting information and relevant opinions on the agro-ecological production, processing, marketing, and consumption of food, food networks and craft production. Chapter IV presents the conclusions and recommendations of the study regarding the contribution to food sovereignty in the parish through the production, processing, marketing and consumption of traditional products of farm families in the area. At the end, conclusions and recommendations were presented in regards to the contribution of the study to food sovereignty in the parish through production, processing, marketing and consumption of traditional products of rural families in the area.